Sierra Leone : Evaluation of the Technical Assistance Program (November 2001 to November 2004) for the Bank of Sierra Leone. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
Over the period 2001-2004, Sierra Leone was a major recipient of MFD Technical Assistance, generally among the 10 countries in the world receiving the most assistance. This involvement represented a substantial contribution by the IMF towards the reconstruction of the country after the devastating civil war that ended in 2000.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: BSL Staff; MFD; PP; Program; Staff; Sierra Leone